Nature writing : (Norton, 2002)
Man's encounter with nature has produced some of the great literature of our time. Darwin's ruminations on the Galapagos Islands, Melville's exploration of the "whiteness of the whale, " and Thoreau's communion with Walden Pond are monuments in the history of writing and thought. "The Norton Book of Nature Writing, " including 125 selections by 94 writers, is the fist definitive and comprehensive collection of the many voices of nature writing which have flourished in English and American over the last two hundred years.